Normatywne uwarunkowania rozwoju gospodarczego: f Przypadek krajów prawosławnych - Kutyło, Łukasz (Przegla̜d religioznawczy, 2015)
Over one hundred years ago Max Weber formulated his well-known thesis, in which he assumed that Protestant ethos played an important role in the economic development of North Europe. The German scholar described mechanisms responsible for this process. In his reflections, however, he paid attention to their cultural manifestations. It was unfortunate, because it seems that these mechanisms have universal character and they could be activated in every religious tradition. Thanks to them a society is able to mobilize its members and achieve some objectives. They both discipline and integrate people as well as direct their attention and activity toward social fields important for this mobilization. In the text a subject of interest is a presence of these mechanisms in European Orthodox Christian countries. They are usually less developed than both European Catholic as well as Protestant states. According to Weberian thesis, their economic underdevelopment is a consequence of specific ethos, which is contradictory to "the spirit of capitalism." In order to examine this assumption there were conducted the analyses on data coming from European Value Studies. The text includes their outcomes.